1987
DOI: 10.1016/0035-9203(87)90378-6
|View full text |Cite
|
Sign up to set email alerts
|

Arboviral causes of non-specific fever and myalgia in a fever hospital patient population in Cairo, Egypt

Abstract: Fever and myalgia are non-specific clinical manifestations of illness which commonly occur in patients with arboviral disease. In Egypt, such illness is often mis-diagnosed as "influenza". To determine arboviral aetiology in patients admitted with fever and myalgia, acute and convalescent sera samples were obtained from 55 patients admitted with these clinical manifestations to the Imbaba Fever Hospital, Giza, Egypt, during October and November 1984. Based on viral isolation, and a comparison of acute and conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Convalescent sera results were reported in two AFI studies, neither of which was positive as indicated by a four-fold rise in antibody titers [37, 38]. One study reporting detection of CHIKV in mosquito pools was identified in our search, in which CHIKV was detected by RT-qPCR in 26.6% of 11 pools of 30 Ae .…”
Section: Resultsmentioning
confidence: 96%
“…Convalescent sera results were reported in two AFI studies, neither of which was positive as indicated by a four-fold rise in antibody titers [37, 38]. One study reporting detection of CHIKV in mosquito pools was identified in our search, in which CHIKV was detected by RT-qPCR in 26.6% of 11 pools of 30 Ae .…”
Section: Resultsmentioning
confidence: 96%
“…SFS and SFN generally cause a febrile illness with headaches lasting for several days [7,14,20,21], whereas TOS infection is characterized by high fever, severe headaches, and aseptic meningitis with long convalescence [16][17][18]22]. At present, only a few cases of TOS infection have been reported in individuals from nonendemic areas [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Seroprevalence studies performed with human or vertebrate sera indicates that SFSV, or a closely related one, is circulating in Jordan [26], Israel [27], Sudan [28], Tunisia [29], Pakistan [30], Egypt [31], Bangladesh [32], Iran [33]. At the outset of this study, the most comprehensive serological study did not detect the presence of neutralizing antibodies reactive to SFSV in human sera of Algerian populations of Tamanrasset and Djanet [34].…”
Section: Discussionmentioning
confidence: 99%